Harmonic reduction methods for electrical generation: a review - Fallows, Daniel; Nuzzo, Stefano; Costabeber, Alessando; Galea, Michael (IET, 2018)
This paper provides a comprehensive literature review of techniques for harmonic related power quality improvement of electrical generation systems. An increasing interest in these aspects is due to the ever more stringent power quality requirements, deriving from new grid codes and compliancy standards, aimed at limiting waveform harmonic distortion at all points of the distribution network. Although a wealth of literature is available for such techniques, it has never been compiled into a handbook incorporating all the solutions aimed at both electrical machine and power systems engineers.